2021
DOI: 10.1002/cssc.202101498
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Electron‐Transfer Kinetics in Magnesium Electrolytes: Influence of the Solvent on the Battery Performance

Abstract: The performance of rechargeable magnesium batteries is strongly dependent on the choice of electrolyte. The desolvation of multivalent cations usually goes along with high energy barriers, which can have a crucial impact on the plating reaction. This can lead to significantly higher overpotentials for magnesium deposition compared to magnesium dissolution. In this work we combine experimental measurements with DFT calculations and continuum modelling to analyze Mg deposition in various solvents. Jointly, these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 70 publications
1
31
0
Order By: Relevance
“…[58] Drews et al developed a kinetic model coupling the desolvation to electron transfer at metal Mg anode. [59] They demonstrated that it is not necessary to peel the entire solvent molecule from the solvated magnesium cation before the first step of reduction. As shown in Figure 5(g and h), the Mg[B-(Ohfip) 4 ] 2 /DME and/DG demonstrate huge similarities in the desolvation process.…”
Section: Anode-electrolyte Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…[58] Drews et al developed a kinetic model coupling the desolvation to electron transfer at metal Mg anode. [59] They demonstrated that it is not necessary to peel the entire solvent molecule from the solvated magnesium cation before the first step of reduction. As shown in Figure 5(g and h), the Mg[B-(Ohfip) 4 ] 2 /DME and/DG demonstrate huge similarities in the desolvation process.…”
Section: Anode-electrolyte Interfacesmentioning
confidence: 99%
“…Drews et al. developed a kinetic model coupling the de‐solvation to electron transfer at metal Mg anode [59] . They demonstrated that it is not necessary to peel the entire solvent molecule from the solvated magnesium cation before the first step of reduction.…”
Section: Fluorinated Boron–centered Anionsmentioning
confidence: 99%
“…However, the high charge density of the magnesium cations also causes strong coulomb interactions with anions as well as solvent molecules and therefore the kinetic barriers for desolvation and solid-state diffusion are much higher than for lithium ions. [1,[9][10][11][12] Consequently, the choice of suitable electrolytes and cathode materials is not straightforward. Reversible magnesium insertion with reasonable kinetics was possible for the first time with a Chevrel Phase (CP) cathode (Mo 6 S 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…[15,23] In general, the desolvation of the electroactive specie is an important step, which can kinetically hinder the electrochemical reaction at the anode as well as at the cathode side. [1,9,10,[38][39][40][41] Thereby, the presence of chloride anions is also beneficial for the desolvation process. [1,9,10,42,43] However, the corrosive nature of the chlorides is an issue for commercializing magnesium batteries and therefore research increasingly focuses on chloride-free electrolyte systems, whereby the stateof-the-art electrolytes are based on the non-nucleophilic magnesium tetrakis(hexafluoroisopropyloxy)borate salt Mg[B-(hfip) 4 ] 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[1] Moreover, energetic barriers for desolvation and solid-state diffusion of the double-charged magnesium ion are usually very high, which can have a crucial impact on the battery performance. Former can significantly hinder the electron-transfer reaction, [2] whereas latter makes the choice of suitable cathode materials very challenging. Consequently, a good understanding of the limiting processes in rechargeable magnesium batteries is key to develop novel high-capacity / high-voltage cathode materials.…”
mentioning
confidence: 99%